Drawing the Line: Same-sex adoption and the jurisprudence of the ECtHR on the application of the “European consensus” standard under Article 14 - Junko Nozawa (Utrecht Journal of International and European Law, 2013)
One of the main criteria that the European Court of Human Rights uses in determining the parameters of the margin of appreciation has been to find a consensus among the state parties to the Convention as to the definition or interpretation of a specific right.  The way the Court has implemented the methodology of finding a "European consensus" of the discriminatory practice of states under Article 14 has been problematic. Firstly, it is unclear when the Court takes into consideration the practice of member states of the European Council. Secondly, it is unclear how it defines the comparative group and the threshold necessary in defining a consensus. This note looks at the application of the Court of this standard in cases concerning same-sex adoption in light of its most recent decision in X. and Others v. Austria (2013). It is argued that the application of the standard in practice has yielded variable jurisprudence, is inconsistently applied, and risks further fragmenting Contracting States' obligations under the Convention. In using the consensus standard as an interpretive comparative tool, the Court should allow a narrow margin of appreciation only where there is substantial consensus on an issue. It is the author's position that its negative iteration, or the notion that a lack of consensus should yield a wide margin, should not be maintained, as this approach risks further deteriorating the protection of fundamental rights.